O reflexo da criação do selo fiscal de controle de água nos botijões de 10 litros e 20 litros para além da arrecadação de ICMS no Estado do Ceará - Nogueira, Sandra Sindeaux (2023)
This dissertation seeks to understand the impact on ICMS collection of a tax incentive measure for enterprises in the bottled water sector in the state of Ceará. In 2017, the State Government released a decree in which it reduced the ICMS rate for companies that met certain requirements, such as a minimum number of people employed. To achieve this objective, we used a Bai and Perron structural break test to find out if there was a structural break at times close to this period. Next, a multiple linear regression was estimated to capture the effect of these breaks on ICMS collection. The results indicated a break in periods close to the tax changes. Next, when analyzing the structure of the multiple regression, a positive effect of these structural breaks was found on the collection of ICMS/Água.